Severe Prolonged Dysphagia following Transoral Resection of Bilateral Synchronous Tonsillar Carcinoma. (23rd August 2013) - Patel, Alpen B.; Pollei, Taylor R.; Hinni, Michael L.; Moore, Eric J.; Hayden, Richard E.
Abstract : Objectives: 1) Describe the complication of severe dysphagia following transoral surgical resection for bilateral simultaneous or synchronous tonsillar squamous cell carcinoma. 2) Analyze the incidence of bilateral simultaneous or synchronous tonsillar squamous cell carcinoma, as well as tumor multifocality in the setting of human papillomavirus. Methods: A retrospective review of four patients who presented to an academic, tertiary referral center between 2008‐2012 were reviewed; two treated with transoral laser microsurgery (TLM) and two with transoral robotic surgery (TORS) for biopsy proven previously untreated bilateral primary squamous cell carcinoma (SCCA). Main outcome measures included functional swallowing determined by the Functional Outcome Swallowing Scale (FOSS). The incidence of significant postoperative complications was recorded. Results: Two patients had surgery for discontiguous involvement of bilateral palatine tonsils with SCCA, while two patients had surgery for bilateral tonsillar SCCA with unilateral extension into the base of tongue. Complete swallowing failure as characterized by the FOSS was seen postoperatively in 3/4 patients who underwent TLM or TORS for bilateral simultaneous tonsillar carcinoma, while one patient was lost to follow‐up. Conclusions: Severe dysphagia in the setting of bilateral oropharyngectomy for simultaneous or synchronous tonsillar SCCA is rarely described but a significant concern. In an era with increased use of transoral surgery, along with increased human papillomavirus incidence, this unusual complication warrants discussion.